2013
DOI: 10.1038/jid.2012.468
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Utility of Circulating Tumor Cells in Metastatic Cutaneous Melanoma

Abstract: The incidence of melanoma is increasing worldwide. Advances in targeted agents and immunotherapy have improved outcomes in metastatic disease, but biomarkers are required to optimize treatment. We determined the prevalence of circulating tumor cells (CTCs) and explored their utility as prognostic and pharmacodynamic biomarkers. A total of 101 patients with metastatic cutaneous melanoma were recruited prospectively. CTC number was determined using the CellSearch platform and melanoma kits in samples taken at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
127
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 25 publications
12
127
1
5
Order By: Relevance
“…Based on the validated HMW-MAA antigen detection, 22,23 uveal melanoma CTC count was lower than in most epithelial tumor types, but was in line with previous results obtained in metastatic cutaneous melanoma patients. 18 Our results showed that elevated CTC count, using either a 1 or 2 CTC=7.5 mL positivity threshold, is associated with survival in our prospective Figure 1.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Based on the validated HMW-MAA antigen detection, 22,23 uveal melanoma CTC count was lower than in most epithelial tumor types, but was in line with previous results obtained in metastatic cutaneous melanoma patients. 18 Our results showed that elevated CTC count, using either a 1 or 2 CTC=7.5 mL positivity threshold, is associated with survival in our prospective Figure 1.…”
Section: Discussionmentioning
confidence: 51%
“…It has been reported previously in cutaneous melanoma patients, together with its sensitivity and reproducibility. 17,18 Briefly, cells expressing CD146 were immunomagnetically enriched and stained with 4,2-diamidino-2-phenylindole dihydrochloride (DAPI), phycoerythrin-conjugated antibody (clone 9.2.27) that binds to HMW-MAA and a mixture of two allophycocyaninconjugated antibodies to identify leukocytes (CD45, clone HI30) and endothelial cells (CD34, clone 581). To be counted as a melanoma CTC, a cell must have an oval morphology and a nucleus [DAPI (1)], together with a HMW-MAA(1), CD45(2) and CD34(2) phenotype.…”
Section: Ctc Countmentioning
confidence: 99%
See 1 more Smart Citation
“…The PFS and OS were both shorter in patients with unfavorable CTM. (21,22 ). Besides, the study that demonstrated that CTC numbers were associated with shorter survival in pancreatic cancer had limited cases (20 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, there are no existent biomarkers, which could anticipate this phenomenon (3). Longitudinal follow-up of patients and monitoring of circulating tumor cell (CTC) levels could predict treatment failure and help switch to another type of treatment (4)(5)(6).…”
Section: Accepted For Publication 6 January 2016mentioning
confidence: 99%